THE INFLUENCE OF WORKING CAPITAL MANAGEMENT ON PROFITABILITY: EVIDENCE FROM THE MANUFACTURING SECTOR - Muhammad Al Faridho Awwal (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
This study aims to examine the effect of working capital management on the profitability of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. Working capital is proxied through three main components, namely accounts receivable turnover, inventory turnover, and accounts payable, while profitability is measured using Return on Assets (ROA) and Net Profit Margin (NPM). The research method used is a quantitative approach with a causal- comparative type of research and panel data regression analysis techniques to identify cause-and-effect relationships between variables. The research results indicate that the effectiveness of managing receivables and inventory significantly positively affects the company's profitability, while the use of trade credit as short-term financing also contributes positively if managed proportionally. This research emphasizes the importance of integrated working capital management strategies to enhance operational efficiency and the competitiveness of companies in the manufacturing sector. The implications of these findings provide practical guidance for financial managers in designing optimal working capital policies to achieve sustainable profitability.